Managing internal growth at Vedanta Group - Agarwal, Promila, (SAGE business cases., 2020)
The case describes the internal growth workshop (IGW) initiative at Vedanta Group. Anil Agarwal in 1976 founded Vedanta as a scrap-metal dealership in Mumbai (then Bombay). Over the years, Anil pursued a very aggressive growth journey with a vision to create a leading global natural resource company. The principal objective of discussing this case is to understand how Vedanta introduced this initiative and how it fits within the strategic human resource management (SHRM) at the group.